Gemcitabine Combination Nano Therapies for Pancreatic Cancer - Kamalika Samanta; Saini Setua; Sonam Kumari; Meena Jaggi; Murali M. Yallapu; Subhash C. Chauhan (MDPI AG, 2019)
Pancreatic cancer is one of the deadliest causes of cancer-related death in the United States, with a 5-year overall survival rate of 6 to 8%. These statistics suggest that immediate medical attention is needed. Gemcitabine (GEM) is the gold standard first-line single chemotherapy agent for pancreatic cancer but, after a few months, cells develop chemoresistance. Multiple clinical and experimental investigations have demonstrated that a combination or co-administration of other drugs as chemotherapies with GEM lead to superior therapeutic benefits. However, such combination therapies often induce severe systemic toxicities. Thus, developing strategies to deliver a combination of chemotherapeutic agents more securely to patients is needed. Nanoparticle-mediated delivery can offer to load a cocktail of drugs, increase stability and availability, on-demand and tumor-specific delivery while minimizing chemotherapy-associated adverse effects. This review discusses the available drugs being co-administered with GEM and the limitations associated during the process of co-administration. This review also helps in providing knowledge of the significant number of delivery platforms being used to overcome problems related to gemcitabine-based co-delivery of other chemotherapeutic drugs, thereby focusing on how nanocarriers have been fabricated, considering the modes of action, targeting receptors, pharmacology of chemo drugs incorporated with GEM, and the differences in the physiological environment where the targeting is to be done. This review also documents the focus on novel mucin-targeted nanotechnology which is under development for pancreatic cancer therapy.